-5x-4(-3x+15)=3

Simple and best practice solution for -5x-4(-3x+15)=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5x-4(-3x+15)=3 equation:


Simplifying
-5x + -4(-3x + 15) = 3

Reorder the terms:
-5x + -4(15 + -3x) = 3
-5x + (15 * -4 + -3x * -4) = 3
-5x + (-60 + 12x) = 3

Reorder the terms:
-60 + -5x + 12x = 3

Combine like terms: -5x + 12x = 7x
-60 + 7x = 3

Solving
-60 + 7x = 3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '60' to each side of the equation.
-60 + 60 + 7x = 3 + 60

Combine like terms: -60 + 60 = 0
0 + 7x = 3 + 60
7x = 3 + 60

Combine like terms: 3 + 60 = 63
7x = 63

Divide each side by '7'.
x = 9

Simplifying
x = 9

See similar equations:

| -6(-v-3y+4)= | | 2x^2-4x+4=25 | | 0.8x-4=1.5x+0.2 | | 48.15/45 | | 0.8x-4=1.5+0.2 | | f(x)=x^4+8x^2-12 | | x^2-2x=10.5 | | 3x+4(-4x+16)=8 | | 3x+10=2x+x+18 | | 4+33x=95 | | xsquared-2x=10.5 | | -2x+4x=56 | | -29+(-25)= | | 3(2u+7)=-12+8u | | 85/5= | | 7(2x-5)=4(6x-2)+x | | 2/3m-10=-12 | | 3x^2+81x-972=0 | | 10x+30=10x+60 | | 3(t)+1(n)=9 | | x+3(-10)=-9 | | 5(t)+3(n)=19 | | W/2-3=8 | | W/2-3=- | | -2x-10-2x=2(x+4) | | 7(2x-5)=(6x-2)+x | | 2a+6+6a-3= | | 9x+2x=x+26 | | 25p=3 | | 2x-6=(1/2)(4x-6) | | y=c+20 | | 7/23-9/23 |

Equations solver categories